2006
DOI: 10.1001/archpsyc.63.10.1139
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenology of Children and Adolescents With Bipolar Spectrum Disorders

Abstract: Children and adolescents with BP-II and BP-NOS have a phenotype that is on a continuum with that of youth with BP-I. Elevated mood is a common feature of youth with BP-spectrum illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
430
0
15

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 454 publications
(472 citation statements)
references
References 36 publications
(37 reference statements)
21
430
0
15
Order By: Relevance
“…Strober et al (1995) reported that five years after hospitalization, 22% of adolescents with BPD had SUD, though no further description of the SUD or comparison with controls were available. More recently, Axelson et al (2006) reported a 10% rate of SUD in a younger sample of BPD although no control groups were available for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Strober et al (1995) reported that five years after hospitalization, 22% of adolescents with BPD had SUD, though no further description of the SUD or comparison with controls were available. More recently, Axelson et al (2006) reported a 10% rate of SUD in a younger sample of BPD although no control groups were available for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Her depressive symptoms were often present in a residual form, both between episodes of major depression and during manic episodes, leading to an overall mixed bipolar presentation. Sarah's mixed symptom presentation is frequent among other children with BD (Kraepelin 1921;Axelson et al 2006;Duax et al 2007;Algorta et al 2011). Mixed presentations result in greater psychosocial impairment and can lead to an enhanced risk of suicide as a result of the coupling of dysphoric mood and hopelessness, with elevated energy and impulsivity (Algorta et al 2011).…”
Section: Figmentioning
confidence: 99%
“…Indeed, these patients have a high risk for substance abuse, legal problems and suicide attempts. [50][51][52][53] The main factors associated with poor BD prognosis are the following: earlier age of onset, duration of symptoms, rapid cycling, mixed episodes, psychotic symptoms, comorbidities such as ADHD and anxiety disorders, low socioeconomic status, negative life events, presence of psychiatric disorders in the family, absence of psychotherapy, low adherence to pharmacological treatment, use of antidepressants and alcohol. [45][46][47][48][54][55][56] …”
Section: Epidemiologymentioning
confidence: 99%